Phylogenomic analyses of Sapindales support new family relationships, rapid Mid-Cretaceous Hothouse diversification, and heterogeneous histories of gene duplication - Joyce, Elizabeth M.; Appelhans, Marc S.; Buerki, Sven; Cheek, Martin; de Vos, Jurriaan M.; Pirani, José R.; Zuntini, Alexandre R.; Bachelier, Julien B.; Bayly, Michael J.; Callmander, Martin W.; Devecchi, Marcelo F.; Pell, Susan K.; et al. (Frontiers in Plant Science, 2023)
Sapindales is an angiosperm order of high economic and ecological value comprising nine families, c. 479 genera and c. 6570 species. However, family and subfamily relationships in Sapindales remain unclear, making reconstruction of the order’s spatio-temporal and morphological evolution difficult. In this study, we used Angiosperms353 target capture data to generate the most densely sampled phylogenetic trees of Sapindales to date, with 448 samples and c. 85% of genera represented. The percentage of paralogous loci and allele divergence was characterised across the phylogeny, which was time-calibrated using 29 rigorously assessed fossil calibrations. All families were supported as monophyletic. Two core family clades subdivide the order, the first comprising Kirkiaceae, Burseraceae, and Anacardiaceae, the second comprising Simaroubaceae, Meliaceae, and Rutaceae. Kirkiaceae is sister to Burseraceae and Anacardiaceae, and, contrary to current understanding, Simaroubaceae is sister to Meliaceae and Rutaceae. Sapindaceae is placed with Nitrariaceae and Biebersteiniaceae as sister to the core Sapindales families, but the relationships between these families remain unclear, likely due to their rapid and ancient diversification. Sapindales families emerged in rapid succession, coincident with the climatic change of the Mid-Cretaceous Hothouse event. Subfamily and tribal relationships within the major families need revision, particularly in Sapindaceae, Rutaceae and Meliaceae. Much of the difficulty in reconstructing relationships at this level may be caused by the prevalence of paralogous loci, particularly in Meliaceae and Rutaceae, that are likely indicative of ancient genome duplication events such as hybridization and polyploidization playing a role in the evolutionary history of these families. This study provides key insights into factors that may affect phylogenetic reconstructions in Sapindales across multiple scales, and provides a state-of-the-art phylogenetic framework for further research.